THE ROLE OF THE TEACHER TO OVERCOME THE LAZY STUDENTS AT SMA NEGERI 1 ATAMBUA INDONESIA - Melkianus Bisik (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2022)
This qualitative study aimed to (1) knows the factors that cause students to be lazy in learning at SMA Negeri 1 Atambua and (2) know the role of the teacher to overcome those lazy students at SMA Negeri 1 Atambua. The subjects of the study were students, teachers, and vice principals. The data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data display, and drawing conclusions. The study showed that the factors that cause students to be lazy in learning, such as being full of assignments, learning methods, social environment, cellphone, social media, and poorly organized classrooms. Thus, there were 4 students who only got scores of 63, 66, 64, and 68, while the standard minimum criteria (KKM) was 70. Besides, teachers provided direct personal guidance and visited the students to overcome the lazy students in learning.